2013
DOI: 10.1088/0004-637x/779/2/94
|View full text |Cite
|
Sign up to set email alerts
|

Globular Cluster Scale Sizes in Giant Galaxies: The Case of M87 and the Role of Orbital Anisotropy and Tidal Filling

Abstract: We present new Hubble Space Telescope imaging of the outer regions of M87 in order to study its globular cluster (GC) population out to large galactocentric distances. We discuss particularly the relationship between GC effective radii r h and projected galactocentric distance R gc . The observations suggest a shallow trend r h ∝ R 0.14 gc out to R gc ∼ 100 kpc, in agreement with studies of other giant elliptical galaxies. To theoretically reproduce this relationship we simulate GC populations with various dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
2
12
0
1
Order By: Relevance
“…Nevertheless, the great majority of GCs are smaller than r h ∼ 10 pc; in the Virgo cluster, which lies at a distance of 16.5 Mpc (Mei et al 2005;Blakeslee et al 2009), the average GC half-light radius is 2.7 ± 0.35 pc ∼ 0. 035 , similar results can be found in Webb et al 2013). By contrast, the half-light radii of known UCDs span a range, from 11 pc to 93 pc with a median of ∼ 20 pc or 0.…”
Section: Measurement Of Half-light Radii: Methodologysupporting
confidence: 81%
“…Nevertheless, the great majority of GCs are smaller than r h ∼ 10 pc; in the Virgo cluster, which lies at a distance of 16.5 Mpc (Mei et al 2005;Blakeslee et al 2009), the average GC half-light radius is 2.7 ± 0.35 pc ∼ 0. 035 , similar results can be found in Webb et al 2013). By contrast, the half-light radii of known UCDs span a range, from 11 pc to 93 pc with a median of ∼ 20 pc or 0.…”
Section: Measurement Of Half-light Radii: Methodologysupporting
confidence: 81%
“…The finding that UCDs in the central ∼ 40 kpc are depleted of radial orbits may be partly attributed to a stronger tidal influence at smaller galactocentric distances. To be quantitative, the Jacobi radius r J of a stellar cluster moving in the tidal field of its host galaxy is determined by its galactocentric distance r gal , the galaxy mass M gal interior to r gal and the cluster mass m. Specifically, r J = r gal (m/2M gal ) 1/3 (von Hoerner 1957;Innanen et al 1983;Bertin & Varri 2008;Renaud et al 2011;Webb et al 2013). Based on this basic tidal theory and the Zhu et al mass profile of M87, we estimated the ratio of limiting radius r L to r J as a function of galactocentric distances for M87 UCDs (m = 2×10 6 M ⊙ or 5×10 6 M ⊙ ) with projected half-mass radius r h = 10 pc ( Figure 21).…”
Section: Depletion Of Radial Orbits Of Ucds At Small Galactocentric Dmentioning
confidence: 99%
“…Additionally, even though cluster sizes are measured in different wave bands, many studies have found that there are minimal differences when comparing sizes measured with different filters (e.g. Harris 2010;Strader et al 2012;Webb et al 2013b). And, since similar constraints are used to confirm GC candidates and minimize contaminants (magnitude, colour, quality of fit, and size), the observational datasets are as homogeneous as possible.…”
Section: Observationsmentioning
confidence: 99%
“…M87 is a giant elliptical galaxy located at the centre of the Virgo cluster, with a distance modulus of (m − M )0 = 30.88 (Pierce et al 1994;Tonry et al 2001 Webb et al (2012) and Webb et al (2013b) for a detailed description of how cluster candidates are selected and sizes are measured.…”
Section: M87mentioning
confidence: 99%
See 1 more Smart Citation